UVB drives different stages of epigenome alterations during progression of skin cancer. (1st May 2019) - Yang, Yuqing; Wu, Renyi; Sargsyan, Davit; Yin, Ran; Kuo, Hsiao-Chen; Yang, Irene; Wang, Lujing; Cheng, David; Wang, Chao; Li, Shanyi; Hudlikar, Rasika; Lu, Yaoping; et al.
Abstract: Exposure to ultraviolet B (UVB) irradiation results in multitude of cellular responses including generation of reactive oxygen species and DNA damage and is responsible for non-melanoma skin cancers (NMSCs). Although genetic mutation is well documented, the epi-mutation, the alteration in epigenetics, remains elusive. In this study, we utilized CpG Methyl-seq to identify a genome-wide DNA CpG methylation, to profile the DNA methylation in UVB-irradiated SKH-1 mouse skin epidermis and non-melanoma skin papillomas at various stages. Methyl-seq and RNA-seq were performed to examine the methylation and corresponding transcriptome alterations. The methylation profiles in mouse epidermis were altered by UVB-irradiation as time progresses. Ingenuity Pathways Analysis (IPA) identified many cancer related pathways including PTEN, p53, Nrf2 and inflammatory signaling in UVB-irradiation induced carcinogenesis. Additionally, some novel genes involved in skin carcinogenesis that were not previously reported were differentially methylated, including Enf2, Mgst2, Vegfa, and Cdk4. Taken together, the current study provides novel profiles and insights of methylation and transcriptomic changes at different stages of carcinogenesis in UVB-irradiation induced NMSC and offers potential targets for prevention and treatment of NMSC at different stages of human skin cancer. Highlights: DNA methylation was altered by both UVB irradiation and aging, while RNA expression was mainly affected by UVB irradiation. A list of key genes involved in UVB-induced carcinogenesis were identified with concomitant DNA CpG methylation changes. This study provides novel profiles of CpG methylation and transcriptomic changes at different stages of UVB-induced skin cancer. This study offers potential targets for prevention/treatment of human skin cancer.